2003
DOI: 10.1002/cne.10732
|View full text |Cite
|
Sign up to set email alerts
|

Identification of spinal neurons involved in the urethrogenital reflex in the female rat

Abstract: The urethrogenital (UG) reflex is a spinal sexual reflex that consists of autonomic and somatic nerve activity and vaginal, uterine, and anal sphincter contractions. The UG reflex is under tonic descending inhibition by neurons in the region of the nucleus paragigantocellularis (nPGi). The location of spinal neurons activated by the UG reflex was examined in the female rat using the immediate early gene, c-fos. In addition, the descending inputs from the nPGi onto fos-activated neurons was examined using the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Stimulation of the pelvic and pudendal nerves in the anesthetized cat resulted in an increase of fos-I nuclei in the superficial dorsal horn and medial gray of S1-S3 [29]. Other studies in females, have reported similar but relatively larger activation patterns of fos-immunoreactivity after vaginocervical stimulation, stimulation of the urethrogenital reflex and noxious stimulation of the bladder [5,6,13,15,26,35,41,58].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Stimulation of the pelvic and pudendal nerves in the anesthetized cat resulted in an increase of fos-I nuclei in the superficial dorsal horn and medial gray of S1-S3 [29]. Other studies in females, have reported similar but relatively larger activation patterns of fos-immunoreactivity after vaginocervical stimulation, stimulation of the urethrogenital reflex and noxious stimulation of the bladder [5,6,13,15,26,35,41,58].…”
Section: Discussionmentioning
confidence: 72%
“…Neuroanatomical studies mapping spinal interneurons involved in pelvic organ function confirm that the DGC and lamina X contain neurons that transverse multiple spinal segments and project to the brain [26,35,36,[39][40][41]. Stimulation of the pudendal nerve and pelvic viscera increases electrophysiological activity of DGC neurons and their dendritic fields [25,30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, spinal circuitry is well conserved across mammalian species, so that pathways identified in laboratory mammals are highly likely to have close homologues in humans. A spinal reflex response to mechanical stimulation of the urethrogenital region, known as urethrogenital reflex (UGR), has been reported in both male and female rats (McKenna et al, 1991;Vathy and Marson, 1998;Marson et al, 2003;Marson and Gravitt, 2004). The responses to the UGR activation in female animals resemble those seen during sexual activity, including significant increases in pelvic blood flow and rhythmic contractions of the vagina and uterus (Bohlen et al, 1982a(Bohlen et al, , 1982bSipski, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of an immediate-early proto-oncogene protein, c-Fos, in spinal cord neurons are increased by activation of nociceptive sensory neurons, providing a valuable tool to identify neurons within spinal nociceptive pathways (Morgan et al, 1987;Marson et al, 2003;Marson and Gravitt, 2004;Coggeshall, 2005;Wiedey et al, 2008;Gao and Ji, 2009;Wang et al, 2010). Indeed, immunohistochemical mapping of c-Fos expression has allowed the identification of several populations of spinal neurons activated by stimulation of pelvic and pudendal nerves as well as the UGR (Marson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%